Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s13197-015-2150-3
|View full text |Cite
|
Sign up to set email alerts
|

Extra virgin olive oil modulates brain docosahexaenoic acid level and oxidative damage caused by 2,4-Dichlorophenoxyacetic acid in rats

Abstract: Oxidative stress is an important pathomechanism of neurological disorders such as Alzheimer disease and Parkinson disease, cardiovascular disorders and many others. This study sought to verify whether extra-virgin olive oil (EVOO), lipophilic fraction (OOLF) and hydrophilic fraction (OOHF) exerted a brain protective effect against the oxidative stress caused by 2,4-dichlorophenoxyacetic acid (2,4-D) pesticide at a dose of 5 mg/kg body weight. 2,4-D, EVOO and its fractions were administered to rats by gavages f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…α-Tocopherol was the major tocopherol identified (Tunisia > Spain > Morocco) and γ-tocopherol was also detected (Spain > Tunisia > Morocco) (Table 1). Of note, previous in vivo experiments have shown that the Tunisian EVOO had protective effects against lipid peroxidation, measured on Wistar rat erythrocytes, liver and brain [60,61,62]. Data obtained on Tunisian EVOO indicate that it could have neuroprotective effects [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…α-Tocopherol was the major tocopherol identified (Tunisia > Spain > Morocco) and γ-tocopherol was also detected (Spain > Tunisia > Morocco) (Table 1). Of note, previous in vivo experiments have shown that the Tunisian EVOO had protective effects against lipid peroxidation, measured on Wistar rat erythrocytes, liver and brain [60,61,62]. Data obtained on Tunisian EVOO indicate that it could have neuroprotective effects [62].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, previous in vivo experiments have shown that the Tunisian EVOO had protective effects against lipid peroxidation, measured on Wistar rat erythrocytes, liver and brain [60,61,62]. Data obtained on Tunisian EVOO indicate that it could have neuroprotective effects [62]. It was therefore of interest to determine the biological activities of major EVOO compounds (OA and tocopherols) on nerve cells.…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies suggested that olive oil exerts a protective effect against cardiovascular diseases, neurological disorders and certain malignant tumors (i.e. breast, prostate, endometrium, digestive tract) due to its well-balanced fatty acids, some trace nutritional components (squalene, phyto-sterols and so on) and natural antioxidants (Ruiz-Canela et al, 2011;Amel et al, 2016;Escrich et al, 2013). Extra virgin olive oil (EVOO) is considered to be the highest quality olive oil, in that it does not undergo any treatment other than washing, decantation, centrifugation and filtration.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of EVOO and high supplementation of corn oil provided modulation effects on breast cancer through a combination of different signaling pathways [121]. In addition, EVOO also possessed neuroprotective activity that may counter the oxidative damage to the brain caused by 2,4-D [122].…”
Section: Olea Europaeamentioning
confidence: 99%